Multicenter study in Turkiye of unsuppressed viremia in people living with human immunodeficiency virus: aegean experience - Ilkay Akbulut; Zeynep Sedef Varol; Veysel Akca; Basak Gol Serin; Emel Erogul; Ilker Odemiş; Seniha Senbayrak; Sabri Atalay (BMC Infectious Diseases)
Abstract Introduction/Objective This Turkish study aimed to investigate the factors that contribute to the failure of virological suppression in people with human immunodeficiency virus (HIV) receiving antiretroviral therapy (ART). The factors evaluated were sociodemographic characteristics, opportunistic infections, polypharmacy, comorbidities, and the ART regimen used. The purpose of this investigation was to obtain important insights that can be utilized to improve treatment strategies at both individual and public health levels. Methods This multicenter retrospective case-control study compared data from 263 patients with suppressed viremia with 125 with unsuppressed viremia, all treated at one of three hospitals in the Aegean region of Turkiye. Sociodemographic and clinical characteristics and ART regimen details were compared between the two groups. Logistic regression analysis was used to identify the predictors of virological failure. Results Patients with unsuppressed viremia were significantly more likely to be older, have lower educational levels, and reside in large cities. Our logistic regression analysis showed that each additional month since HIV diagnosis increased the risk of virological failure by 2%. Moreover, each 1% increase in nadir CD4 + T-cells reduced the risk of virological failure by 4%. Opportunistic infections increased the risk of virological failure by 3.25 times. Interestingly, virological failure was 6.5 times more likely in patients who did not suffer ART side effects. Conclusions This study identified the sociodemographic, clinical, and treatment-related factors that contribute to virological failure in people with HIV in Turkiye. This can be utilized to develop individualized treatment strategies and improve virological control and clinical outcomes.